(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the significance of transitioning from subjective evaluation to objective measurement methods in rhythmic gymnastics. The research highlights the critical roles of anthropometry and dynamometry as primary metrological tools in monitoring an athlete’s physical fitness and body formulation. By analyzing parameters such as body composition, growth dynamics, handgrip strength, and back muscle strength, the study demonstrates how quantitative data minimises human error and enhances training efficiency. Furthermore, the integration of data-driven decisions, statistical norms, and video analysis tools enables coaches to substantiate their conclusions, prevent injuries, and individualise training programs. Ultimately, the article establishes that combining the coach’s intuitive experience with objective sports science elevates the training process to a scientifically grounded pedagogical experiment.